Semester-Based Differentiation of Communication and Collaboration Competencies in Biology Education: A Quantitative Approach - Sumadi, Sri Wahyuni; B, Nurhayati; Faisal, Faisal (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The aim of this study is to analyze the impact of academic semesters on the development of communication and teamwork skills among students in the Biology Education program. Methodology: This study uses a quantitative comparison design with multivariate analysis. Data was collected from 232 students using surveys. Statistical tools and software were employed to analyze the development of communication and teamwork skills across different academic semesters. Main Findings: Communication competency improved significantly from Semester II to Semester IV, indicating meaningful development in the early-to-mid study phases; however, it showed no further gains by Semester VI. In contrast, teamwork competency remained consistently low and did not differ significantly across semesters, suggesting that routine academic progression alone may be insufficient to strengthen collaborative skills. Novelty/Originality of this study: The findings indicate that communication competence may develop through mid-program learning experiences, while teamwork competence requires more intentional and sustained instructional support. This study provides new insights into the development of communication and teamwork skills in Indonesian higher education, highlighting gaps in teamwork development and suggesting the need for educational innovations aligned with MBKM and 21st-century competencies. It contributes to the limited research on skills development across academic levels.